BROADBAND ADOPTION, DIGITAL DIVIDE, AND THE GLOBAL ECONOMIC COMPETITIVENESS OF WESTERN BALKAN COUNTRIES - Mitrović, Đorđe (Economic Annals, 2015)
The existing variation in economic performance between countries is significantly affected by the level, diffusion, and use of different types of information and communication technology. In the last several years economic competitiveness increasingly depends on broadband availability and the adoption, use, and speed of this technology. Broadband access to the internet fosters economic growth and development and increases a country’s global competitiveness. This technology could have a big impact on the competitive advantage of Western Balkan countries because they currently experience a large digital divide, both within countries (between regions, urban and rural areas, different vulnerable groups, etc.) and with EU countries. The purpose of the paper is to analyse the current level and dynamics of the digital divide in Western Balkan countries using the Broadband Achievement Index (BAI), the Data Envelopment Analysis (DEA)-based model, the Global Competitiveness Index (GCI), the Corruption Perception Index (CPI), and cross-country methodology. This paper measures and compares Western Balkan countries’ current level of broadband adoption and their position on the evolutionary path towards closing the existing economic and digital gap with EU countries. Comparative analysis of calculated BAI data values, GCI, and CPI shows that Western Balkan countries belong to the ‘laggard’ group regarding their broadband achievement and global economic competitiveness. The values of the calculated BAI sub-indexes in this paper indicate the strong and weak sides of the corresponding aspects of broadband technology implementation and give directions for setting further priorities for political intervention, not only in the building of information society but also in the improvement of the economic competitiveness of Western Balkan countries.